2018
DOI: 10.1177/1062860618798719
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Care After Implementing a Multifaceted Intervention to Improve Preventive Cardiology Practice in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) increases cardiovascular disease (CVD) risk. However, CVD risk factor identification and treatment is often inadequate. The authors implemented a multifaceted rheumatology practice intervention to improve CVD risk factor measurement, assessment, and management. The intervention included clinician education, point-of-care decision support, feedback, and care management. The authors measured quality indicators from electronic health records and assessed impact with interrupted time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This makes cardiovascular risk assessment (as well as assessment for these associated conditions) that much more important. Improving cardiovascular risk assessment techniques in patients with inflammatory arthritis is challenging and has been a topic of ongoing research [ 61 , 62 ].…”
Section: Management Of Obesity As a Cardiovascular Risk Factor In Psamentioning
confidence: 99%
“…This makes cardiovascular risk assessment (as well as assessment for these associated conditions) that much more important. Improving cardiovascular risk assessment techniques in patients with inflammatory arthritis is challenging and has been a topic of ongoing research [ 61 , 62 ].…”
Section: Management Of Obesity As a Cardiovascular Risk Factor In Psamentioning
confidence: 99%
“…Multifaceted interventions are those with two or more intervention components. Using a multifaceted intervention, a previous study reported that the intervention was effective in promoting disease-monitoring behavior among rheumatoid arthritis patients (Majka et al, 2018). Others validated the IMCHB-based intervention (Hickman, Clochesy, & Alaamri, 2016).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These patients received care from 10 attending rheumatologists, 4 rheumatology fellows, 1 advanced practice nurse, and 2 physician assistants. Most of these clinicians had previously taken part in a prior cardiovascular disease prevention improvement study (16).…”
Section: Methodsmentioning
confidence: 99%
“…Strategies to improve CVD prevention in patients with RA have included the use of a specialty clinic for CVD prevention in patients with inflammatory joint disease (12) and efforts to improve collaborative care between rheumatologists and primary care (13)(14)(15)(16). Previously, we tested implementing a multifaceted quality improvement intervention consisting of clinician education, clinical decision support at the point of care, performance measurement and feed-back to rheumatology clinicians, and individualized mailed recommendations to patients to measure CVD risk factors and to address hypertension, cholesterol treatment, or smoking when applicable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation